Meaning and context in Job and Tobit. (June 2019) - Kwon, JiSeong James
The book of Tobit, which is dated to the Hellenistic period, is often compared with the model of the pious and innocent sufferer in the book of Job which is assumed to be the product of a late Persian or early Hellenistic scribal idea. It has been argued that in many ways, the author of Tobit directly alluded to Job's texts and put its literary framework and themes into a new historical context, the Assyrian Diaspora. However, these literary works are quite dissimilar in how they use various Israelite and non-Israelite materials and they substantially reflect different thoughts and interests. In this article, I indicate how each book understands Jewish the literary tradition and suggest that both books reflect their own intellectual background. This will be discussed in relation to four areas: (1) suffering and theodicy; (2) dialogue; (3) retribution, law, and piety; and (4) election, eschatology, and the apocalyptic.